Breaking Dormancy in Kentia Palm Seeds by Infusion Technique. - Chin, Hoong Fong; Krishnapillay, Baskaran; Alang, Zaleha Christine (1988)
In this investigation three organic solvents, namely dichloromethane, dimethyl sulfoxide (10%) and acetone each containing 100 mgl- 1 gibberellic acid (CA 3) were used to treat the seeds prior to germination, to assess the effecitiveness of these solvents in transporting CA 3 directly to the embryo for triggering an early germination. The results indicate that organic solvents appear effective in transporting the CA 3 to the embryo of Kentia Palm seeds to improve germination with no deleterious effects. The first sign of germination in vitro was observed after 2 months in culture, while the emergence of the plumule in sand was observed around the 4th month of planting. Over the 9-month study period, for the treatment where dichloromethane was used, 85% of the seeds planted in sterile sand had germinated while in in vitro, 90% of the seeds had germinated. It is probable that this approach may prove beneficial in improving the germination time in palm species that exhibit long periods ofdormancy before germination.